2018
DOI: 10.1124/dmd.118.083691
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Directly Affects the Gut Microbiota to Promote Intestinal Farnesoid X Receptor Activation

Abstract: Intestinal bacteria play an important role in bile acid metabolism and in the regulation of multiple host metabolic pathways (e.g., lipid and glucose homeostasis) through modulation of intestinal farnesoid X receptor (FXR) activity. Here, we examined the effect of berberine (BBR), a natural plant alkaloid, on intestinal bacteria using in vitro and in vivo models. In vivo, the metabolomic response and changes in mouse intestinal bacterial communities treated with BBR (100 mg/kg) for 5 days were assessed using N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 48 publications
3
60
0
1
Order By: Relevance
“…However, it has been proved that the main action site of BBR is the gut (Sun et al, 2016). BBR directly impacts the gut microbiota of mice and causes lipid-lowering effects via sequential events (Sun et al, 2016; Tian et al, 2018). It has been also proved that the glucose-lowering effect of BBR in rats is associated with the shift of the gut microbiota structure in BBR-treated rats (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been proved that the main action site of BBR is the gut (Sun et al, 2016). BBR directly impacts the gut microbiota of mice and causes lipid-lowering effects via sequential events (Sun et al, 2016; Tian et al, 2018). It has been also proved that the glucose-lowering effect of BBR in rats is associated with the shift of the gut microbiota structure in BBR-treated rats (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that the action of BBR in rats is associated with the host metabolic phenotypes mediated by the structural modulation of gut microbiota (Zhang et al, 2012; Zhang et al, 2015b; Li et al, 2016; Wang Y. et al, 2017). Furthermore, BBR directly impacts the gut microbiota, thereby altering bile acid metabolism and activating intestinal farnesoid X receptor, which lead to lipid-lowering effects in mice (Sun et al, 2016; Tian et al, 2018). However, the association between the hypoglycemic/hypolipidemic actions of BBR and the gut microbiome in fish remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…and Clostridium spp. ), 20 , 21 and Bacteoidetes-to-Firmicutes ratio and reduction of the gut microbiota diversity. 22 …”
Section: Introductionmentioning
confidence: 99%
“…and Clostridium spp. ), 20,21 and Bacteoidetes-to-Firmicutes ratio and reduction of the gut microbiota diversity. 22 Several studies have suggested that BBR's structural analogs could have similar or improved functions.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Finally, BBR can decrease the expression of fatty acid translocase Cd36 intestinal cells through the farnesoid X receptor (FXR) signal pathway, promoting cholesterol efflux indirectly. 10 , 11 Despite the fact that a preliminary understanding of the molecular mechanism of BBR on lipid regulation is revealed, its specific macromolecule target has not been discovered yet. This greatly limits the structure modification of BBR for improving its hypolipidemic activity.…”
Section: Introductionmentioning
confidence: 99%